2017
DOI: 10.3390/ijms18122694
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Caste-Specific Multi-Layer Defense Mechanism of Formosan Subterranean Termites, Coptotermes formosanus Shiraki

Abstract: The survival and foraging of Coptotermes formosanus Shiraki in a microbe-rich environment reflect the adaptation of an extraordinary, sophisticated defense mechanism by the nest-mates. We aimed to explore the host pathogen interaction by studying caste-specific volatile chemistry and genes encoding the antioxidant defense of winged imagoes, nymphs, soldiers and workers of Formosan subterranean termites. Qualitative analyses of C. formosanus Shiraki performed by HS-SPME/GC-MS showed considerable variations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Results showed significant differences in the SOD activities of date-palm dust mites calculated at different times (F = 48.55; df = 12, 24; P < 0.0001), with different fungal isolates (F = 85.27; df = 2, 24; P < 0.0001), and their interaction (F = 356.29; df = 4, 24; P < 0.0001) as shown in Table 2. The highest SOD activity, as depicted in the present results, among datepalm dust mites at the start of infection agrees with the results of Gretscher et al (2016) and Hussain et al (2017). However, a decline in SOD activities with time from the most virulent isolate 2049, corroborates with AlJabr et al (2018), who suggested that decline in SOD activities at a lateral infection stage from virulent isolates led to ROS elimination failure.…”
Section: Evaluation Of Oligonychus Afrasiaticus Antioxidant Defense Msupporting
confidence: 92%
See 1 more Smart Citation
“…Results showed significant differences in the SOD activities of date-palm dust mites calculated at different times (F = 48.55; df = 12, 24; P < 0.0001), with different fungal isolates (F = 85.27; df = 2, 24; P < 0.0001), and their interaction (F = 356.29; df = 4, 24; P < 0.0001) as shown in Table 2. The highest SOD activity, as depicted in the present results, among datepalm dust mites at the start of infection agrees with the results of Gretscher et al (2016) and Hussain et al (2017). However, a decline in SOD activities with time from the most virulent isolate 2049, corroborates with AlJabr et al (2018), who suggested that decline in SOD activities at a lateral infection stage from virulent isolates led to ROS elimination failure.…”
Section: Evaluation Of Oligonychus Afrasiaticus Antioxidant Defense Msupporting
confidence: 92%
“…1). Similarly, enhanced mortality response of 2049 over time was reported against Coptotermes formosanus Shiraki (Hussain et al 2017) and Ocinara varians Walker (Hussain et al 2009). These findings showed that the effectiveness of 2049 in terms of pathogenicity against all these hosts revealed a valuable feature of being a broad-spectrum mycopathogen.…”
Section: Pathogenicity Assessment Of Metarhizium Anisopliae Isolatesmentioning
confidence: 55%
“…The built-in antioxidant defense mechanism protects the biological systems by regulating ROS production. However, stressful situations disproportionate the target host intrinsic antioxidants and ROS balance by eliciting oxidative stress [ 22 , 43 ]. The target host has evolved accordingly antioxidant defense system to maintain homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of fungal pathogens into the Integrated Pest Management program of O. afrasiaticus attained particular attention because of host specificity, persistence in target host population, numerous isolates and eco-friendly [ 18 ]. Entomopathogenic fungi especially isolates of Beauveria bassiana are well-known for their pathogenicity against different target pest species [ 19 , 20 , 21 , 22 ]. Spores of the isolates of entomopathogenic fungi impart mortality in the target pest by overcoming the complicated host defense related multiple mechanisms [ 18 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potato dextrose agar plates (90-mm × 15 mm) with different concentrations (0.80, 1.60, 2.40, 3.20, and 4.00 mg/mL) of 1-Chlorooctadecane were prepared as described in detail by a previous study [45] Ten microliter spores suspension of M. anisopliae EBCL 02049 at a single concentration (1 × 10 6 spores/mL) were pipetted in the center of each PDA-plate. The plates after inoculation were sealed with parafilm.…”
Section: Compatibility Of M Anisopliae Spores With 1-chlorooctadecanementioning
confidence: 99%